Upregulation of Early and Downregulation of Terminal Pathway Complement Genes in Subcutaneous Adipose Tissue and Adipocytes in Acquired Obesity - Kaye, Sanna; Lokki, A. Inkeri; Hanttu, Anna; Nissilä, Eija; Heinonen, Sini; Hakkarainen, Antti; Lundbom, Jesper; Lundbom, Nina; Saarinen, Lilli; Tynninen, Olli; Muniandy, Maheswary; Rissanen, Aila; et al. (Frontiers in Immunology, 2017)
Inflammation is an important mediator of obesity-related complications such as the metabolic syndrome but its causes and mechanisms are unknown. As the complement system is a key mediator of inflammation, we studied whether it is activated in acquired obesity in subcutaneous adipose tissue and isolated adipocytes. We used a special study design of genetically matched controls of lean and heavy groups, rare monozygotic twin pairs discordant for BMI (n=26, within-pair difference (in body mass index, kg/m2with as much as 18 kg mean weight. Additionally, 14 BMI-concordant (kg/m2) served as a reference group. The detailed measurements included body composition (DEXA), fat distribution (MRI), glucose, insulin, adipokines, C3a and SC5b-9 levels and the expression of complement and insulin signaling pathway-related genes in adipose tissue and adipocytes. In both adipose tissue and isolated adipocytes, the classical and alternative pathway genes were upregulated, and the terminal pathway genes downregulated in the heavier co-twins of the BMI-discordant pairs. The up-regulated genes included C1q, C1s, C2, ficolin-1, factor H, receptors for C3a and C5a (C5aR1) and the iC3b receptor (CR3). While the terminal pathway components C5 and C6 were downregulated, its inhibitor clusterin was upregulated. Complement gene up-regulation in adipose tissue and adipocytes correlated positively with adiposity and hyperinsulinemia, and negatively with the expression of insulin signaling related genes. Plasma C3a, but not SC5b-9, levels were elevated in the heavier co-twins. There were no differences between the co-twins in BMI-concordant pairs. Obesity is associated with increased expression of the early, but not late, complement pathway components and of key receptors. The twins with acquired obesity have therefore an inflated inflammatory activity in the adipose tissue. The results suggest that complement is likely involved in orchestrating clearance of apoptotic debris and inflammation in the adipose tissue.